Hybrid Algoritma Genetik dan Hill Climbing untuk Permasalahan Pengepakan Segi Empat Dua Dimensi - I., Herlia Istiqomah (Jurnal Matematika dan Ilmu Pengetahuan Alam, 2015)
Rectangular packing problem described as n item that will be packed to a single object (which is bigger) to get the pack order of items into an object so that will minimize used object height. Hybrid of genetic algorithm and hill climbing is an algorithm that combines the process of genetic algorithm with hill climbing. Generally, the process of genetic algorithm is generate the first population, evaluation of chromosome, selection, crossover, and mutation. In this thesis, selection process used is roulette wheel, crossover process used is order based crossover, and hill climbing process used as replacement of mutation process. Thereâs 3 kinds of data being used and solve with Java programming language using Netbeans IDE 7.2 software. Using hybrid of genetic algorithm and hill climbing with Java programming language, achieved minimum height from used object is 17 for data with 10 items and object width 20. Second data with 49 items and object width 60, the minimum height achieved is 64. And the last with 97 items and object width 80, the minimum height achieved is 130.Keywords: Two Dimensional Rectangular Packing Problem, Genetic Algorithm, Hill Climbing, and Hybrid.